Detection improvement for anti-collision radar - Qu, Yao Wen (2008)
This thesis illustrates the necessity and design process of performance improvement for radar detection by using novel CFAR detectors. A qualitative discussion of the need for and applications of conventional CFAR detectors is presented first. Typical applications are given as examples of where the radar system may be utilized. A closer look under the Swerling 2 assumption is presented as well. The second portion of the thesis generally introduce the underlying electromagnetic theories that radar detection is built upon. The radar range equation, radar cross section, noise in systems, and vehicular applications are explained. The portion focuses on the radar detection.